2022
DOI: 10.3390/coatings12030414
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Titanium by Femtosecond Laser in Reducing Bacterial Colonization

Abstract: In the past few decades, titanium and its alloys have been widely used in the orthopaedic field. However, because titanium is bioinert and lacks antibacterial properties, infection may happen when bacteria attach to implant surfaces and form biofilms. It has been studied that some naturally existing micron-scale topographies can reduce bacterial attachment such as cicada wings and gecko skins. The aim of this in vitro study was to find an implant with good biocompatibility and antimicrobial properties by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, within the observed inhibitory effects, significant differences were noted in the behavior of the two species on the PCL surfaces, namely a high proliferation growth rate of E. coli compared to that of S. aureus. Previous studies also reported that bacterial responses to underlying surface topography are highly species-and strain-dependent, including in femtosecond-laser-modified surfaces [52,54]. These differences in the antibacterial activity of S. aureus and E. coli are related to the structure and composition of the cell wall in Gram-positive and negative bacteria.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, within the observed inhibitory effects, significant differences were noted in the behavior of the two species on the PCL surfaces, namely a high proliferation growth rate of E. coli compared to that of S. aureus. Previous studies also reported that bacterial responses to underlying surface topography are highly species-and strain-dependent, including in femtosecond-laser-modified surfaces [52,54]. These differences in the antibacterial activity of S. aureus and E. coli are related to the structure and composition of the cell wall in Gram-positive and negative bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…Antibacterial activity associated with topographical features is advantageous for its long-term effects as it retains its anti-adhesive effects and/or elicits mechano-inhibitory effects after bacteria attachment, i.e., morphological abnormalities and cell lysis [51]. Femtosecond-laser-induced microtopographies have been reported to influence bacterial cell attachment, colonization, and biofilm formation for both Gram-positive and Gram-negative bacteria [52][53][54]. Furthermore, the type of laser-induced pattern (such as pillar-like, honeycomb, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Laser surface treatment is also effective for metallic materials. [172][173][174][175] Boinovich et al [59] have produced superhydrophilic and superhydrophobic structures. The former is more effective against E. coli due to stronger adhesion between the rough laser-treated surface and bacteria cell wall, which results in high tension and cell wall rupturing.…”
Section: Biomimetic Micro/nano Topographymentioning
confidence: 99%
“…Laser surface treatment is also effective for metallic materials. [ 172–175 ] Boinovich et al. [ 59 ] have produced superhydrophilic and superhydrophobic structures.…”
Section: Biomimetic Surfaces Inspired By Naturementioning
confidence: 99%
“…where 𝑁 is the number of pulses acting on the same spot. For the sake of compactness, instead of writing two different linear regression models [14], [15], it is possible to formulate equations (3)-( 4), in a comprehensive way [16] as follows:…”
Section: Introductionmentioning
confidence: 99%